PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOSERBA DI KEBUMEN - Husnul Hotimah; Ivo Novitaningtyas (Universitas Bandar Lampung (UBL), 2022)
The increasing development of the retail business in Indonesia has resulted in fierce competition among retail companies. With this, retail companies will increase their marketing activities, in particular, such as service quality and promotion. The purpose of this study was to determine the effect of service quality and promotion on consumer purchasing decisions. This research uses quantitative research methods. The data collection was obtained through the distribution of questionnaires to visitors to the Kebumen Jadi Baru Department Store. The sample in this study collected 97 respondents with a sampling technique that is accidental sampling. Analysis of the data used in this study is multiple linear regression with IBM SPSS version 25. The results of this study state that service quality has a positive and significant effect on purchasing decisions. Promotion has a positive and significant effect on purchasing decisions. Moreover, service quality and promotion have a simultaneous effect on purchasing decisions.